Phytochemical screening and evaluation of antibacterial, anticandidal, and sporicidal properties of Euphorbia tirucalli extract in Terengganu, Malaysia - Abd Wahab, Noor Zarina; Malza, Nur Maizatul Najwa; Rukayadi, Yaya (Bogor Agricultural University, 2024)
Euphorbia tirucalli, commonly known as the pencil cactus or milk bush plant, is used as an alternative medicine. The current study evaluated the phytochemical contents, antibacterial, anticandidal, and antisporicidal potential of the E. tirucalli methanolic extract. The antibacterial and anticandidal activity of E. tirucalli methanolic extract was determined by performing a disc diffusion assay, MIC, MBC, and MCC. The sporicidal activity was tested at different concentrations of extract and exposure times. Phytochemical analyses revealed the presence of alkaloids, saponins, cardiac glycosides, terpenoids, and tannins in E. tirucalli methanolic extract. Results demonstrated inhibition zones of the extract against Gram-positive bacteria were in range of 22.00-7.00 mm. Meanwhile, inhibition zones of the extract against Gram-negative bacteria were in range of 13.00-7.00 mm. All bacteria were inhibited with MIC values at 1.56-25.0 mg/ml and can be completely killed with MBC values of 20-200 mg/ml. Inhibition zones of E. tirucalli methanolic extract against Candida spp. were in the range of 20.00-8.00 mm. All Candida spp. were inhibited with MIC values at 1.56-100.00 mg/ml and MBC values of 100-300 mg/ml. All concentrations of the extract inhibited all Bacillus spp. spores at different exposure times. In conclusion, the methanolic extract of E. tirucalli exhibits antibacterial, anticandidal, and sporicidal activities. The findings indicated that the methanolic extract of E. tirucalli has good potential for prospective nature-based antimicrobial agents. © 2024, Bogor Agricultural University.